(untitled) (Journal of the College of Education for Women, 2022)
Euphemism is an important linguistic phenomenon that tends to soften written or oral expressions. Thus, when translators or interpreters face expressions including euphemism, they need to know how to deal with them. The problem of the current paper lies in the effect of rendering euphemistic expressions inaccurately, as such expressions represent the cultural and terminological sense of the original language. Thus, rendering them improperly will affect the sense of the interpreted speech. For this, it is essential for translators in general and simultaneous interpreters in particular to know the importance of utilizing euphemism in the simultaneous interpreting field, which is the main aim of this paper. To this end, a systematic review has been adopted by shedding light on euphemism types suggested by Williams’ (1975), and euphemism functions suggested by Wijana and Rohmadi (2008), and Nordquist (2018). Some examples were drawn from the common euphemistic topics in which euphemistic expressions and their translation were discussed. This study has concluded that to convey the sense and cultural meaning of the original euphemistic expression, simultaneous interpreters must be aware of the types and functions of such euphemism. This is because the previous knowledge of them plays a positive role in the performance of simultaneous interpreters.